REREADING HADITH OF MAHRAM AND WOMEN’S MOBILITY IN INDONESIAN CONTEXT - Nikmatullah, Nikmatullah; Istianah, Istianah (RIWAYAH, 2024)
The differences in Muslim understanding of mahram impact women’s mobility in the public sphere. This study aims to map the diversity of interpretations on mahram hadith among Indonesian Muslims viewed from the interpretation of arguments and their influence on women’s lives. Through qualitative research, the data was obtained from online media, which was strengthened by interviews, and analyzed by using content analysis. The study results show that mahram is understood textually and contextually with three categories, namely family mahram, which impacts prohibitions, restrictions on women outside the home, and restraint on women in public spaces. Whereas mahram, as a friend and community, functions as a support system for protection for women, which is supported by the state’s security system, affecting women’s freedom in travel and public spaces. The arguments influencing this understanding are different arguments, interpretations, schools of thought, and individual experiences. In the Indonesian context, progressive ulemas reinterpret mahram traditions from personal protection to communal and state protection through three methods, namely reciprocal interpretation, considering context, and using maqashid sharia. The understanding of mahram is not only related to protecting women while traveling but extends to all women’s activities in the public sphere, including worship. Thus, the issue of mahram in the Indonesian context is inseparable from religious, social, cultural, and political discourse.[Perbedaan  pemahaman umat Islam  tentang mahram berdampak pada mobilitas perempuan di ruang publik. Penelitian ini bertujuan untuk memetakan keberagaman penafsiran hadis mahram di kalangan umat Islam Indonesia dilihat dari penafsiran dalil dan pengaruhnya terhadap kehidupan perempuan. Melalui penelitian kualitatif, data diperoleh dari media daring yang diperkuat dengan wawancara, dan dianalisis dengan menggunakan analisis isi. Hasil penelitian menunjukkan bahwa mahram dipahami secara tekstual dan kontekstual dengan tiga kategori, yaitu mahram keluarga yang berdampak pada larangan, pembatasan bagi perempuan di luar rumah, dan pengekangan bagi perempuan di ruang publik. Sedangkan mahram sebagai sahabat dan masyarakat berfungsi sebagai sistem pendukung perlindungan bagi perempuan yang didukung oleh sistem keamanan negara, sehingga memengaruhi kebebasan perempuan dalam bepergian dan ruang publik. Dalil yang memengaruhi pemahaman tersebut adalah perbedaan argumen, penafsiran, mazhab pemikiran, dan pengalaman individu. Dalam konteks Indonesia, ulama progresif menafsirkan kembali tradisi mahram dari perlindungan pribadi menjadi perlindungan komunal dan negara melalui tiga metode, yaitu penafsiran resiprokal, mempertimbangkan konteks, dan menggunakan maqashid syariah. Pemahaman tentang mahram tidak hanya terkait dengan perlindungan terhadap perempuan saat bepergian, tetapi meluas ke seluruh aktivitas perempuan di ruang publik, termasuk beribadah. Dengan demikian, persoalan mahram dalam konteks Indonesia tidak dapat dipisahkan dari wacana keagamaan, sosial, budaya, dan politik.]